Optimization of operational parameters for dust separa - ALI, MUDASIR; DIXIT, A K; MANES, G S; SINGH, M; VERMA, A (The Indian Journal of Agricultural Sciences, 2022)
Straw obtained after mechanical harvesting with combine contains foreign matter like dust which makes it unhealthy for milch animals. An attempt was made to develop a dust separation system for wheat straw combine at Department of Farm Machinery and Power Engineering, PAU Ludhiana during 2019–20. The study involved optimisation of operational parameters for effective dust separation system in wheat straw combine and evaluation of optimized dust separation system under field conditions. The laboratory evaluation of sieve setup was carried for three sieve sizes (3 mm, 4mm, 5 mm), three ossciliations (300, 350, 400 spm) and two residue load conditions (0.572 kg, 0.738 kg). Sieve setup consisted of variable drive system with control unit and electric motor of 2.0 kW having rotational speed of 1500 rpm. The operational parameter, sieve opening size ɸ5 mm and sieve oscillations 400 spm was found better to give the straw quality parameters such as ash content, acid insoluble ash and dust concentration in the range of 8.60–8.77%, 5.14–5.90% and 5.44–6.30%, respectively. The developed system will help in reducing the dust concentration in the wheat straw during harvesting.